Panton-Valentine leukocidin and biofilm production of Staphylococcus aureus isolated from respiratory tract - KARAHASAN, AYŞEGÜL (J INFECTION DEVELOPING COUNTRIES, 2013)
Introduction: Staphylococcus aureus is one of the first bacteria colonizing in cystic fibrosis (CF) respiratory tract and different virulence factors are responsible for disease progression. It is not clear if CF S. aureus strains are more virulent than strains isolated from non-CF patients. Methodology: Biofilm production was detected by a modified tissue culture plate method, presence of genes encoding for Panton-Valentine leukocidin (PVL) was investigated by a signal amplified sandwich hybridization assay and antimicrobial susceptibility patterns were detected by disk diffusion method. Results: Staphylococcus aureus clinical isolates (n = 88) recovered from respiratory tract specimens in which 31 of them were from cystic fibrosis (CF) patients were analysed. Biofilm production was detected in 96.8% of CF isolates in which 32.3% exhibited strong positive phenotype and in 47.4% of non-CF isolates in which strong positive phenotype was not observed (p < 0.05). All CF isolates were methicillin susceptible, whereas 53.4% of non-CF isolates (n = 31) were methicillin resistant. No resistance was observed for vancomycin, chloramphenicol and trimethoprim/sulfamethoxazole in any of the isolates. PVL genes were detected only in two isolates (2.3%), one from each group, CF and non-CF, which both were methicillin susceptible Conclusion: Biofilm rather than PVL production appears to be an important virulence factor in CF patients.
Keywords: Cystic fibrosis; Panton-Valentine leukocidin; antimicrobial; biofilm; CYSTIC-FIBROSIS; YOUNG-CHILDREN; INFLAMMATION; PREVALENCE; INFECTION; PNEUMONIA